Model Breakthrough Technologies as a Tool to Support Import Substitution in the Pharmaceutical Industry - Ogorodova, Lyudmila M.; Golant, Zakhar M.; Tarasov, Igor N.; Narkevich, Igor A.; Lin, Aleksandr A.; Kartashova, Nadezhda S. (International Review of Management and Marketing, 2016)
In this article, the authors posed and solved one of the major issues that dramatically affect the definition of the strategy of advancing development in the industry - are there any in the segment of breakthrough technologies for the production of synthetic Active Pharmaceutical Ingredients (API) highly efficient new technologies can on the one hand to provide the lowest operating costs at a stable and safe production of API good quality and in the required amount according to the Russian portfolio of promising drugs and on the other hand, what should be the role of government and development institutions to ensure full and accelerated implementation of these breakthrough technologies in advanced domestic production sites. The authors noted that in the Russian Federation introduced a model of innovative regional clusters (Pilot innovative territorial clusters in Russia, 2013) is the most effective for achieving the scientific and technological cooperation on the development of breakthrough technologies. Keywords: active pharmaceutical ingredients, governmental support, micro-reactor synthesis JEL Classifications: L69; O10